2008
DOI: 10.1016/j.yjmcc.2008.02.279
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived pluripotent very small embryonic-like stem cells (VSELs) are mobilized after acute myocardial infarction

Abstract: The adult bone marrow (BM) harbors Sca-1+/Lin−/CD45− pluripotent very small embryonic-like stem cells (VSELs), which can differentiate in vitro into several lineages, including cardiac and vascular lineages. Since mobilization of stem/progenitors from the BM is a prerequisite for their participation in organ repair, we investigated whether VSELs are mobilized into the peripheral blood (PB) after acute myocardial infarction (MI). Wild-type mice (C57/BL6 strain, 6-or 15-wk-old) underwent a 30-min coronary occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 35 publications
1
49
0
4
Order By: Relevance
“…32 Interestingly, this adult stem cell can be mobilized and recruited to injured tissues. 36,37 These observations, coupled with previous reports, suggest that Epo increases the stem cell pool in bone marrow and contributes to local bone regeneration induced by BMPs. 38,39 In line with the increase in hematopoietic-related progenitor cells, Epo treatment increased the number of osteoclasts that are derived from the hematopoietic lineage (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…32 Interestingly, this adult stem cell can be mobilized and recruited to injured tissues. 36,37 These observations, coupled with previous reports, suggest that Epo increases the stem cell pool in bone marrow and contributes to local bone regeneration induced by BMPs. 38,39 In line with the increase in hematopoietic-related progenitor cells, Epo treatment increased the number of osteoclasts that are derived from the hematopoietic lineage (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Their presence amongst the MSCs in the Wharton's jelly is in agreement with observations made by other groups that MSCs contain a sub-population of more primitive stem cells [52] or even as postulated by Taichman and group [53] that VSELs are precursors of MSCs. Various studies have also reported that VSELs are mobilized into peripheral blood in response to injury/ stress in animal models [27,[54][55][56] as well as in humans [28][29][30]57] -thus suggesting a role in regeneration and homeostasis.…”
Section: Developmental Origin Of Vselsmentioning
confidence: 99%
“…During this research, the mobilization of these cells from BM to PB after liver and skeletal muscle damage was confirmed. Mobilization of VSELs after acute myocardial infarction has been proved in mice and human beings with a maximum peak at 48 and 24 h respectively [77,78]. Since injured tissue upregulates stromal derived factor-1 (SDF-1) expression, they are thought to migrate towards damaged organs in a SDF-1 chemotactic fashion.…”
Section: Vselsmentioning
confidence: 99%